Management of West Kalimantan Provincial Museum in Supporting History Learning - Busro, Muhammad; Zakso, Amrazi; Putri, Astrini Eka (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This research aims to describe the management of West Kalimantan Province museums in supporting history learning. This research uses a qualitative method with a descriptive approach. The data collection techniques used were observation, interviews and documentation. Data analysis uses data reduction, data presentation and drawing conclusions. Meanwhile, testing the validity of the data uses source triangulation and technical triangulation techniques. The research results show that the form of management carried out by the West Kalimantan Provincial Museum consists of administrative management, collection management, and library management. In supporting historical learning, the West Kalimantan Provincial Museum has created an educational service program, holding exhibitions is an activity that is held as a medium for conveying information and communicating museum collection objects to the public and visitors and collaborating with several educational agencies to develop educational programs that are integrated with historical learning. Educational services related to the collections exhibited in the museum by providing labeling for each collection and providing presentations from museum guides.